Design and Analysis of Digitally Tunable Transconductance Amplifier (DTTA) Using CNTFETs - Shailendra Kumar Tripathi; Sarfraz Hussain; Raj Kumar; Sourabh Sahu (The Scientific World Journal)
Carbon nanotube-FETs (CNTFETs) have become a potential challenger because of their exceptional electrical properties and compatibility with conventional CMOS technology. The design and study of digitally tunable transconductance amplifiers (DTTAs) using CNTFETs are the main topics of this work. By utilizing the special characteristics of CNTFETs, the suggested DTTA design makes transconductance tunable, providing a versatile method of adjusting amplifier settings without requiring modifications to the hardware architecture. This study provides a complete description of the CNTFET modeling techniques utilized for realistic circuit simulations, along with a detailed analysis of the DTTA based on CNTFETs. The circuit is implemented using a 32 nm CNTFET model and verified results with HSPICE.